Phosphorus distribution between rare earth oxides containing slags and ferromanganese alloy. (28th May 2019) - Xi, Xiaojun; Yang, Shufeng; Li, Jingshe; Luo, Diqiang; Cai, Xina; Lai, Chaobin
ABSTRACT: In this paper, factors influencing the phosphorus distribution ratio between RE oxides containing slags and ferromanganese were studied. The results demonstrated that phosphorus distribution ratio values between RE oxides containing slags and ferromanganese are higher than those between CaO-based slags and ferromanganese. An increase in the temperature leads to a decrease in the phosphorus distribution ratio, and the downward trend is more pronounced when the temperature increases above 1673 K (1400°C). An increase of RE oxide content in the pre-melted slags, and of the oxygen partial pressure of the experimental system, improves the phosphorus distribution ratio. It was also found that when the Si content is below 0.25 wt-%, there is almost no change in the phosphorus distribution ratio; however, the phosphorus distribution ratio decreases as the Si contents increases further.